The Theoretical Aspects of the Company’s Capital Structure - Koliesnichenko, Anastasiia; Bilgen, S. (Видавничий дім "ІНЖЕК", 2023)
The article examines the concept of enterprise capital in view of the significant problems of the theoretical aspects of the capital structure. It is defined that the capital structure covers many aspects of not only financial, but also operational and investment activities. Theories of capital structure are considered. Four main theories are specified according to the evolution of the capital structure: the Modigliani and Miller theory, the peking order theory, the trade-off theory, and the agency theory. The authors substantiate such elements of the concept of capital structure of enterprise as: assets, debt, own funds, borrowed funds, profitability, financial sustainability, risk, financial reporting. On the basis of the carried out analysis of the main theoretical aspects of the capital structure of enterprise already studied by scientists, the most significant problems of formation of the optimal capital structure and the influence of age and size of enterprise on the construction of the structure are allocated. In addition, a separate role in the management of the company’s capital structure is played by its financial and investment policy. The capital structure is a powerful indicator of the impact on the ratio of return on assets and equity, determines the system of coefficients of financial stability and solvency and, ultimately, forms the ratio of the degree of profitability and risk in the process of enterprise development. In accordance with the specified circumstances, the main directions of improving the capital structure of the company are formulated as follows: improvement of accounts receivable; improvement of accounts payable; price management in interaction with suppliers; cost reduction; segmentation and credit risk analysis. As a conclusion, it is noted that the most important task of companies is to determine the optimal capital structure of the enterprise and its most effective use in order to improve the efficiency of the enterprise as a whole.

У статті досліджено поняття капіталу підприємства з огляду на суттєві проблеми теоретичних аспектів структури капіталу. Визначено, що структура капіталу охоплює багато аспектів не лише фінансової, а й операційної та інвестиційної діяльності. Розглянуто теорії структури капіталу. Відзначено чотири основні теорії відповідно до еволюції структури капіталу: теорія Модільяні та Міллера, теорія ділового порядку, теорія торгівлі та теорія агентства. Обґрунтовано такі елементи поняття структури капіталу підприємства, як: активи, борг, власні кошти, позикові кошти, прибутковість, фінансова стійкість, ризик, фінансова звітність. На основі аналізу досліджених науковцями основних теоретичних аспектів структури капіталу підприємства виділено як найбільш суттєві проблеми формування оптимальної структури капіталу та вплив віку та розміру підприємства на побудову структури. Крім того, окрему роль в управлінні структурою капіталу компанії відіграє її фінансова та інвестиційна політика. Структура капіталу є потужним індикатором впливу на співвідношення рентабельності активів і власного капіталу, визначає систему коефіцієнтів фінансової стійкості та платоспроможності й у кінцевому підсумку формує співвідношення ступеня прибутковості та ризику в процесі розвитку підприємства. Відповідно до зазначених обставин сформульовано основні напрями поліпшення структури капіталу компанії: поліпшення дебіторської заборгованості; поліпшення кредиторської заборгованості; управління цінами у взаємодії з постачальниками; зниження витрат; сегментація та аналіз кредитного ризику. У підсумку зазначено, що найважливішим завданням компаній є визначення оптимальної структури капіталу підприємства та найбільш ефективного його використання з метою підвищення ефективності діяльності підприємства загалом.
Теоретичні аспекти структури капіталу компанії
Keywords: capital structure; структура капіталу; capital structure theories; assets; debt; equity; borrowed funds; profitability; financial and investment policy; прибутковість; теорії структури капіталу; активи; борги; власні кошти; позикові кошти; фінансова та інвестиційна політика